CONCEPTUAL DELIMITATIONS REGARDING THE SALES FORECASTING METHODS. CASE STUDY FOR THE SEASONAL COEFFICIENT METHOD - Dragomirescu, Simona Elena; Solomon, Daniela Cristina (Studies and Scientific Researches. Economics Edition, 2014)
One of the most important stages in the budget drafting process is the sales forecasting. As a matter of fact, the sales affect the whole activity of a company, their variation being considered the main risk factor for the performance and the financial position of the company. Sales forecasting starts with analyzing the turnover over a longer period of time. It includes all the studies and calculations made in order to determine the potential market to which the company can get access, as well as the part of it that the company is estimated to cover. There are several methods for planning the amount of sales, each company being able to choose one or more such methods. All the sales forecasting methods have advantages and disadvantages; however, in practice it was proved that most large companies use a combination of several methods. However, when there are seasonal variations each year, the seasonal coefficient method is used in order to forecast the sales. The exemplification of this method is done on the level of an production industrial company.